Variation in the risk of colorectal cancer in families with Lynch syndrome: a retrospective cohort study. Issue 7 (July 2021) - ,; Win, Aung Ko; Dowty, James G.; Reece, Jeanette C.; Lee, Grant; Templeton, Allyson S.; Plazzer, John-Paul; Buchanan, Daniel D.; Akagi, Kiwamu; Aksoy, Seçil; Alonso, Angel; Alvarez, Karin; et al.
Summary: Background: Existing clinical practice guidelines for carriers of pathogenic variants of DNA mismatch repair genes (Lynch syndrome) are based on the mean age-specific cumulative risk (penetrance) of colorectal cancer for all carriers of pathogenic variants in the same gene. We aimed to estimate the variation in the penetrance of colorectal cancer between carriers of pathogenic variants in the same gene by sex and continent of residence. Methods: In this retrospective cohort study, we sourced data from the International Mismatch Repair Consortium, which comprises 273 members from 122 research centres or clinics in 32 countries from six continents who are involved in Lynch syndrome research. Families with at least three members and at least one confirmed carrier of a pathogenic or likely pathogenic variant in a DNA mismatch repair gene ( MLH1, MSH2, MSH6, or PMS2 ) were included. The families of probands with known de-novo pathogenic variants were excluded. Data were collected on the method of ascertainment of the family, sex, carrier status, cancer diagnoses, and ages at the time of pedigree collection and at last contact or death. We used a segregation analysis conditioned on ascertainment to estimate the mean penetrance of colorectal cancer and modelled unmeasured polygenic factors to estimate the variation in penetrance. The existence of unknown familial risk factors modifying colorectal cancer risk for Lynch syndrome carriers was tested by use of a Wald p value for the null hypothesis that the polygenic SD is zero. Findings: 5585 families with Lynch syndrome from 22 countries were eligible for the analysis. Of these, there were insufficient numbers to estimate penetrance for Asia and South America, and for those with EPCAM variants. Therefore, we used data (collected between July 11, 2014, and Dec 31, 2018) from 5255 families (1829 MLH1, 2179 MSH2, 798 MSH6, and 449 PMS2 ), comprising 79 809 relatives, recruited in 15 countries in North America, Europe, and Australasia. There was strong evidence of the existence of unknown familial risk factors modifying colorectal cancer risk for Lynch syndrome carriers (p<0·0001 for each of the three three continents). These familial risk factors resulted in a wide within-gene variation in the risk of colorectal cancer for men and women from each continent who all carried pathogenic variants in the same gene or the MSH2 c.942+3A>T variant. The variation was especially prominent for MLH1 and MSH2 variant carriers, depending on gene, sex and continent, with 7–56% of carriers having a colorectal cancer penetrance of less than 20%, 9–44% having a penetrance of more than 80%, and only 10–19% having a penetrance of 40–60%. Interpretation: Our study findings highlight the important role of risk modifiers, which could lead to personalised risk assessments for precision prevention and early detection of colorectal cancer for people with Lynch syndrome. Funding: National Health and Medical Research Council, Australia.